STRATEGIES FOR DETERMINING QUANTITY AND QUALITY SCALES IN ORDER TO IMPROVE LEARNING EVALUATION - Tamami, Fauziyah Qurrota Ayun; Anshari, Ari; Rahmawati, Siti (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Learning evaluation cannot be separated from the educational process which plays an important role in determining the effectiveness of the teaching and learning process and the achievement of educational goals. Effective evaluation measures not only the quantity of student achievement, but also the quality of their understanding. This article examines the strategy of determining the scale of quantity and quality in order to improve learning evaluation at SMA Muhammadiyah 2 Surakarta. The main focus is on the integration of quantitative and qualitative research to provide a comprehensive picture of student progress. This research uses a qualitative approach with descriptive methods of analysis and field. Data were collected through observation, in-depth interviews with teachers, students, and principals, and analysis of related documentation. The results of this study show that this strategy successfully increases the motivation and participation of Shiva, as well as developing critical thinking skills and application of knowledge. The implementation of this strategy has a positive impact on improving the quality of learning. The findings of this study also provide satisfaction from students and parents with an evaluation system that is considered more fair and accurate. Through this approach, SMA Muhammadiyah 2 Surakarta successfully provides quality education, prepares students with the practical skills necessary to succeed in the world of work, and adapts learning methods relevant to global demands.